2013
DOI: 10.1002/j.0022-0337.2013.77.11.tb05617.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of E–Mail Communication Skills Among First– and Fourth–Year Dental Students

Abstract: As e-mail and other forms of electronic communication increase in popularity, it is important for dental schools to consider a curriculum that prepares their graduates to understand and apply effective electronic communication strategies to their patients. Relecting this shift in communication behavior, the American Medical Association has developed speciic e-mail communication guidelines. Some behavioral examples in these guidelines include protecting patients' protected health information (PHI), ensuring pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The total email etiquette scores were 62.21 out of 100 and the global impression of politeness scores were 2.6 out of 4. Researchers have already shown that being a so-called “digital native” is an insufficient condition for professional email writing [ 3 ]. The results of this study are comparable with previous literature, such as one that evaluated introductory biology class students and demonstrated their email format scores to be less than eight points out of 13 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total email etiquette scores were 62.21 out of 100 and the global impression of politeness scores were 2.6 out of 4. Researchers have already shown that being a so-called “digital native” is an insufficient condition for professional email writing [ 3 ]. The results of this study are comparable with previous literature, such as one that evaluated introductory biology class students and demonstrated their email format scores to be less than eight points out of 13 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emails have become commonplace in doctors’ routine work, including communicating with their patients, obtaining consultations from other specialists, and collaborating with other researchers on scholarly projects [ 1 ]. Similarly, emails are commonly used in medical education as the usual method of communication between faculty members and students and sometimes they are even developed as a teaching tool to cultivate communication skills or professionalism [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Email communication provides a valuable tool for provider-patient interactions when used appropriately and in a secure manner. In fact, many patients prefer communicating with their health care provider via email [ 20 ] because it expands opportunities for consultation, treatment, and patient care [ 38 ]. Email has been described as environmentally and economically friendly, as well as efficient because it quickly connects the individuals providing and receiving care [ 46 ].…”
Section: Email Use In a Clinical Settingmentioning
confidence: 99%
“…Cyberincivility is defined as communicative behavior against social norms that is exhibited in computer-mediated interactions, such as those involving email and text messages, or on online social networking sites [ 17 ]. Because health professional students who demonstrate cyberincivility in school appear to continue the same behavior after they complete their education [ 18 - 20 ], prelicensure education on email netiquette is especially important. In spite of the need, training in email netiquette is not occurring consistently and is not having consistent results in interprofessional discipline training programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation